Efeito do estádio de maturação na qualidade da silagem de milho na resposta econômica de novilhos confinados - Oliveira, Marcos Rogério (2010)
This assay was carried out at State University of Center-West. The aim of this study was to evaluate the corn silages at different maturation stages, from the plant production to the animal performance of steers in feedlot condition. About the plant production, the objective was to evaluate the corn plant morphological, structural and nutritional characteristics at different maturation stages. The maturation stage advancement afforded increasing rates face the silage with 25,6% of DM, with respectively, average daily drying of 0,4531% of dry matter (DM) on bracts and cob, 1,2835% of DM on grains and 0,3953% of DM on the plant. The maturation stage with 32,6% of DM afforded higher green matter (GM) (62.234 vs. 50.565 kg/ha), DM (20.288 vs. 12.944 kg/ha) and grains (8.329 vs. 3.100 kg/ha) production, decreased the neutral detergent fiber (55,08 vs. 50,55% of DM) and increased the energetic density (2,843 vs. 3,067 Mcal/kg of digestible energy), consequently, lower production costs of GM (49,20 vs. 59,03 R$/t of GM), DM (150,93 vs. 230,61 R$/t of DM) and total digestible nutrients (TDN) (217,63 vs. 356,29 R$/t of TDN) were presented, if compared to the silage with 25,6% of DM respectively. For animal performance, the aim was to evaluate 24 steers crossbreeding Charolais x Nellore in feedlot, feed with diets including silage of corn at two different maturation stages (25,6 vs. 32,6% of DM) associated to two levels of concentrate inclusion (40 vs. 70%). The corn silage at 25,6% of DM stage determined lower biological efficiency, independent on the concentrate level. The increasing from 40 to 70% in concentrate level associated to the silage of corn at 32,6% of DM use didn’t cause any change for animal performance. The maturation stage manipulation and the concentrate level in the diet didn’t show any difference for the carcass yield of bovine finished in feedlot. Because the ensiling at 32,6% of DM stage affords better exploration of the productive potential of GM, DM and TDN/ha, it causes lower unit production costs and higher roughage quality, to guarantee a higher profitability for the feedlot beef cattle system.